Implementation of Pikukuh Karuhun in the Behavior of Baduy Youths at Cibeo after being Exposed to Digital Communication Media - Santa Lorita Simamora; Dicky Andika; Nurhayani Saragih; Moh. Nor Shahizan Ali (Ikatan Sarjana Komunikasi Indonesia, 2023)
The main purpose of this journal is to describe the cultural change in the practice of Pikukuh Karuhun (The Law of Baduy people that governs their relation with nature). While most of the people of Inner Baduy (locally known as Baduy Dalam) in Cibeo still strongly clings into these ancient laws, the youths of said village have started to use technologies in their daily lives, most often to communicate with guests who planned to visit their village. The researchers of this journal tried to study this change that occurs in Cibeo’s youths, specifically about their stance on Pikukuh Karuhun as a local culture that functions to philosophically guide Baduy people on their daily lives. This study was done with ethnomethodology method which is a part qualitative method and constructive paradigm. The results of this research describe the inconsistencies in the practice of Pikukuh Karuhun by Cibeo’s youths that mostly works as local guides and porters in weekends and holidays. They use social media like WhatsApp to communicate with would-be guests before and after their arrival. Their aptitude in using such apps come from their interaction with outlanders that come to visit Cibeo. In-between their interaction with outside visitors, they autodidactly learn to operate phones and social medias as much as they could. Interestingly, researchers found that while they use technology in the form of mobile phones (something that is forbidden by their ancient laws), they only do so outside their village. They never bring their phones into the village but instead they leave it at the hand of their relatives and friends outside Cibeo.